Major brain lesions by intrauterine herpes simplex virus infection: MRI contribution - Duin, L. K.; Willekes, C.; Baldewijns, M. M. L.; Robben, S. G. F.; Offermans, J.; Vles, J. (Prenatal diagnosis, 2007)
The majority of neonatal Herpes Simplex Virus (HSV) infections are acquired at birth as a consequence of direct fetal contact with the infected birth canal or through an ascending infection after premature rupture of the amniotic membranes. Intrauterine transmission of HSV infection from mother to the fetus is rare; in only 5% of the cases it occurs from haematogenous transplacental dissemination. We present a case of transplacental intrauterine HSV infection after a primary maternal HSV infection in the first trimester of pregnancy. The diagnosis was assessed by viral culture and serologic tests. Ultrasound imaging revealed fetal brain damage in the third trimester. Finally, the MRI showed the devastating extensiveness of the HSV infection, which was beyond the expectation based on the ultrasound images. Copyright © 2007 John Wiley & Sons, Ltd.